The Political Economy of Foreign Policy in ECOWAS - Shaw, Timothy M. author. aut Link
XV, 289 p.
Keywords: Both political economy and foreign policy have been transformed in the sixteen states of West Africa at the start of the 1990s because of interrelated external factors (end of the Cold War and start of a New International Division of Labour) and internal factors (national structural adjustment programmes). Sixteen leading analysts of new regional relations, of both cooperation and conflict, offer original revisionist insights into ECOWAS and ECOMOG, debt and democracy, reform and resistance. The mixture of case studies and comparative analyses constitutes a comprehensive overview of West African actors, issues, structures, perspectives and possibilities at the end of the century, with relevance for development discourses and directions in other peripheral regions. Together these offer timely redefinitions and reconceptualisations of central notions like civil society, diplomacy, foreign policy, peacekeeping, security, and self-reliance for political economies and cultures throughout the South.